Canon of Witnesses: Teresa Margolles & The Ethics of Residue - Vale, Dorian (Museum of One, 2025)
Description Canon of Witnesses: Teresa Margolles & The Ethics of Residue By Dorian Vale In this foundational essay, Dorian Vale situates Teresa Margolles within the Canon of Witnesses, a post-interpretive framework that honors artists whose works resist explanation and demand moral proximity. Focusing on Margolles’s use of bodily residue—blood, water from morgues, traces of violence—Vale examines how her practice subverts spectacle and refuses the comfort of metaphor. Rather than aestheticizing death, Margolles preserves its aftermath. Her works do not speak for the dead—they let the materials of death remain unaltered, undecorated, and unresolvable. Through her installations, Vale argues, Margolles becomes a custodian of consequence: holding space for what cannot be revived, only witnessed. Written through the lens of Post-Interpretive Criticism, this essay proposes that Margolles offers one of the most ethically alert practices in contemporary art. Her work is not political commentary—it is aftermath. And in that aftermath, she teaches the critic not to interpret, but to stand still. Vale, Dorian. Canon of Witnesses: Teresa Margolles & The Ethics of Residue. Museum of One, 2025. DOI: 10.5281/zenodo.17070909 Teresa Margolles, Dorian Vale, Post-Interpretive Criticism, Canon of Witnesses, contemporary Mexican artists, art and death, ethical art criticism, trauma in contemporary art, bodily residue in art, morgue water installations, art of aftermath, art and violence, mourning in installation art, witnessing through material, Teresa Margolles analysis, non-interpretive art writing, residue as aesthetic, ethics of witnessing, post-interpretive canon, slow art, sacred presence in contemporary art This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843)
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10438 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 https://africarxiv.ubuntunet.net/handle/1/10466 https://africarxiv.ubuntunet.net/handle/1/10467 https://africarxiv.ubuntunet.net/handle/1/10468 https://africarxiv.ubuntunet.net/handle/1/10469 https://africarxiv.ubuntunet.net/handle/1/10470 https://africarxiv.ubuntunet.net/handle/1/10471 https://africarxiv.ubuntunet.net/handle/1/10472 https://africarxiv.ubuntunet.net/handle/1/10473 https://africarxiv.ubuntunet.net/handle/1/10474 https://africarxiv.ubuntunet.net/handle/1/10475 https://africarxiv.ubuntunet.net/handle/1/10476 https://africarxiv.ubuntunet.net/handle/1/10477 https://africarxiv.ubuntunet.net/handle/1/10478 https://africarxiv.ubuntunet.net/handle/1/10479 https://africarxiv.ubuntunet.net/handle/1/10480 https://africarxiv.ubuntunet.net/handle/1/10481 https://africarxiv.ubuntunet.net/handle/1/10482 https://africarxiv.ubuntunet.net/handle/1/10483 https://africarxiv.ubuntunet.net/handle/1/10484 https://africarxiv.ubuntunet.net/handle/1/10485 https://africarxiv.ubuntunet.net/handle/1/10486 https://africarxiv.ubuntunet.net/handle/1/10487 https://africarxiv.ubuntunet.net/handle/1/10488 https://africarxiv.ubuntunet.net/handle/1/10489 ISSN 2819-7232 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: Interpretation vs. Witnessing; The Viewer as Evidence; Interpretive Restraint; Post-Interpretive Criticism; Art as Ontology; Language as violence; Witness Aesthetics; Restraint in front of art; Quiet philosophy of art; Custodianship of Art; Museum Of One; Ethics in Art Criticism; Visual Culture Studies; Epistemology of witness; Absential Aesthetics; Moral proximity; Custodian of Witness Aesthetics; Presence-Based Criticism; Art as Presence; Art Writer and Theorist; Dorian Vale; Ontology of beauty; Independent Philosopher of Art; Criticism and Reception Theory; Hauntmark Theory; Founder of Post-Interpretive Criticism; Alternative art criticism; Aesthetics; Language as Custody; Radical art restraint; Museum of One; Art Criticism Ethics; Witness over interpretation; Interpretive silence; The Custodian's Oath; Philosophy of Art; Ethical art theory; Interpretation and Meaning; Post-Interpretive Lexicon; Art Theory; Erasure as Afterlife; Epistemology of Art; https://www.museumofone.art/; Aesthetic mercy; Stillmark Theory; The Doctrine of Post-Interpretive Criticism; Art as Truth; Criticism beyond interpretation; Post-Aesthetic Critic; Erasure as ethics; The Canon of Witnesses; Aesthetic Philosopher; Museum of One Manifesto; Silence as method; Comparative Aesthetics; New art criticism movement; Art encounter ethics; Contemporary Aesthetics; Phenomenology and Art